The impact of transnational culture on countering terrorism in Muslim countries: A critical explanation from Tawhidic paradigm (IIUC Business Review, 2022)
This paper tries to address the impact of transnational culture, which is basically consists of cultural diversity, multi-ethnicity, and multi-languages, on countering the terrorism. Transnational culture, through globalization and internationalization, can play a vital role on countering the terrorism both within and across nations, particularly in Muslim-majority nations. For the research purpose, the study obtained the opinions of 59 post graduate students from different universities in Turkey and Bangladesh through a survey on the impact of transnational culture in reducing terrorism. The study found that transnational culture has a significant impact on changing people’s perspective about countering terrorism in today’s Muslim world. The informants also viewed that the Tawhidic paradigm (Unity of God) offers spiritual dimension to educate and nurture people to respect other views, multi-ethnicity, cultures and languages which may lead to counter the terrorism in the Muslim nations. Nevertheless, the results of the study are constrained by the size of the sample and robustness of the analysis.IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 47-60